MALAYSIA’S COMPUTER SCIENCE RESEARCH PRODUCTIVITY BASED ON PUBLICATIONS IN THE WEB OF SCIENCE, 2000-2010 - A., Abrizah; Mee, Chin Wee (Malaysian Journal of Library and Information Science, 2017)
A number of studies have appeared that evaluate the productivity of computer science scholars and their institutions. The aim of this work is to estimate the research productivity of Malaysia’s computer science researchers and their affiliated institutions. To achieve the objectives of the study, we employed the bibliographic repository that is made available to the world’s scientific research, which is the Thomson’s Web of Science (denoted as CWTS-WoS) database. The 903 research works produced by Malaysia’s computer science researchers, published as journal article (74.8 percent) and proceedings (25.2 percent) covered by the database from 2000 to 2010 were evaluated. The productivity of authors and core journals they published in have been determined using Lotka’s and Bradford’s Law. Some of the important findings are that most articles (54.9 percent) are multiauthored, author productivity is not in agreement with Lotka’s law, the maximum number of articles were published in the Lecture Notes of Computer Science, distribution of articles is quite close to Bradford’s Law, and the Multimedia University ranked first for the maximum number of publications (22.3% percent).